High-risk patients with locally advanced non-small cell lung cancer treated with stereotactic body radiation therapy to the peripheral primary combined with conventionally fractionated volumetric arc therapy to the mediastinal lymph nodes - Eichkorn, Tanja; Lischalk, Jonathan W.; Stüwe, Cedric; Tonndorf-Martini, Eric; Schubert, Kai; Dinges, Lisa-Antonia; Regnery, Sebastian; Bozorgmehr, Farastuk; König, Laila; Christopoulos, Petros; Hörner-Rieber, Juliane; Adeberg, Sebastian; et al. (Frontiers in Oncology, 2023)
Introduction: A very narrow therapeutic window exists when delivering curative chemoradiotherapy for inoperable locally advanced non-small cell lung cancer (NSCLC), particularly when large distances exist between areas of gross disease in the thorax. In the present study, we hypothesize that a novel technique of stereotactic body radiation therapy (SBRT) to the primary tumor in combination with volumetric arc therapy (VMAT) to the mediastinal lymph nodes (MLN) is a suitable approach for high-risk patients with large volume geographically distant locally advanced NSCLC. Patients and methods: In this single institutional review, we identified high-risk patients treated between 2014 and 2017 with SBRT to the parenchymal lung primary as well as VMAT to the involved MLN using conventional fractionation. Dosimetrically, comparative plans utilizing VMAT conventionally fractionated delivered to both the primary and MLN were analyzed. Clinically, toxicity (CTCAE version 5.0) and oncologic outcomes were analyzed in detail. Results: A total of 21 patients were identified, 86% (n=18) of which received chemotherapy as a portion of their treatment. As treatment phase was between 2014 and 2017, none of the patients received consolidation immunotherapy. Target volume (PTV) dose coverage (99 vs. 87%) and CTV volume (307 vs. 441 ml) were significantly improved with SBRT+MLN vs. for VMAT alone (p<0.0001). Moreover, low-dose lung (median V5Gy [%]: 71% vs. 77%, p<0.0001), heart (median V5Gy [%]: 41% vs. 49%, p<0.0001) and esophagus (median V30Gy [%]: 54% vs. 55%, p=0.03) dose exposure were all significantly reduced with SBRT+MLN. In contrast, there was no difference observed in high-dose exposure of lungs, heart, and spinal cord. Following SBRT+MLN treatment, we identified only one case of high-grade pneumonitis. As expected, we observed a higher rate of esophagitis with a total of seven patients experience grade 2+ toxicity. Overall, there were no grade 4+ toxicities identified. After a median 3 years follow up, disease progression was observed in 70% of patients irradiated using SBRT+MLN, but never in the spared ‘bridging’ tissue between pulmonary SBRT and mediastinal VMAT. Conclusion: For high risk patients, SBRT+MLN is dosimetrically feasible and can provide an alternative to dose reductions necessitated by otherwise very large target volumes.